Consistency of the Neutralizing Peroxidase Linked Assay for Classical Swine Fever and Homologation with an OIE Reference Laboratory - Santana-Rodríguez, Elaine; Méndez-Orta, Mary Karla; Sardina-González, Talía; Rodríguez-Moltó, María Pilar; Castell- Brizuela, Sara; Sordo-Puga, Yusmel; Pérez-Pérez, Danny; Fundora-Llera, Alianne; Oliva-Cárdenas, Aymé; Vargas-Hernández, Milagros; Duarte, Carlos A.; Frías-Lepoureaux, María Teresa; et al. (International Journal of Scientific Research in Biological Sciences, 2022)
Porvac® is a subunit vaccine against classical swine fever (CSF) that has been recently registered in Cuba. The Neutralizing Peroxidase Linked Assay (NPLA) is the preferred method to measure the levels of neutralizing antibodies (NAb) against classical swine fever virus (CSFV). The purposes of this study were to assess the consistency of the NPLA technique conducted for three years at the Center for Genetic Engineering and Biotechnology (CIGB) and to homologate the performance of the technique with the Nacional Center for Animal Health (CENSA), a reference laboratory for CSF validated by the World Organization for Animal Health (OIE). The consistency of the test was evaluated through two types of systematic controls: the back-titration of the virus stock, and the internal control serum. The 89.3 % of 140 NPLA assays conducted during this period were valid according to the OIE recommendations for the back-titration. The geometric mean of the NAb titre for the internal control was 1628, with lower and upper 95% confidence intervals of 1542 and 1710, respectively. The inter-assay geometric coefficient of variation of the assay was 31.4 %. Finally, a 100% coincidence for CSFV positivity and a statistically significant correlation (Spearman r = 0.78, p < 0.0001) between NAb titres measured at CIGB and CENSA was found after the parallel evaluation of 136 samples from Porvac® vaccinated pigs. Those results indicate that the NPLA assay instrumented at CIGB is robust, highly reproducible, and comparable to a reference laboratory.